2014
DOI: 10.1007/s11033-014-3376-2
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic effects of dipyrido [3,2-a:2′,3′-c] phenazine (dppz) Au(III) complex against diethylnitrosamine/phenobarbital induced experimental hepatocarcinogenesis in rats

Abstract: We evaluated the effects of dipyrido [3,2-a:2',3'-c] phenazine (dppz) Au(III) complex ([Au(dppz)Cl2]Cl) on apoptosis during chemically induced hepatocellular carcinoma. 48 male Spraque-Dawley rats were divided into six groups; group I (control), group II [Dimethyl sulfoxide (DMSO)], group III ([Au(dppz)Cl2]Cl), group IV [diethylnitrosamine + Phenobabital (DEN + PB)], group V (DEN + PB + [Au(dppz)Cl2]Cl (2nd week)), and group VI (DEN + PB + [Au(dppz)Cl2]Cl (7th week). The rats in groups IV through VI were admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…25,26 NDMA and diethylnitrosamines have been reported to cause hepatic carcinogenesis in animals. 27,28…”
Section: Discussionmentioning
confidence: 99%
“…25,26 NDMA and diethylnitrosamines have been reported to cause hepatic carcinogenesis in animals. 27,28…”
Section: Discussionmentioning
confidence: 99%
“…Molecules like dipyrido[3,2-a:2′,3′-c]phenazine (dppz) based ruthenium complexes have been reported as a potential agent in many biological activities such as antitumour, antimicrobial, antiviral, anti-tuberculosis, and anticancer activities. [1][2][3] The utility of such types of metal complexes is completely based on their enormous DNA intercalating nature, excellent redox behavior, good luminescence properties, and extensive photophysical and electrochemical properties. [4][5][6] Over the past few decades, several methods have been developed for the synthesis of dipyrido[3,2-a:2′,3′-c]phenazine (dppz) based ruthenium and iridium complexes from o-phenylenediamine including the use of several organic solvents (methanol, ethanol, acetonitrile, dichloromethane, DMF, etc.…”
Section: Introductionmentioning
confidence: 99%
“…a:2′,3′-c] phenazine]PF 6 (RuL2). Yield: 92%; colour: orange; Mp: 178 °C; R f ( pure methanol): 0.61;1 H NMR (CDCl 3 , 400 MHz): δ 10.38 (d, 2H, H-1, H-10, J = 4.4 Hz, ArH), 9.59 (t, 2H, H-3, H-8, J = 8.0 Hz, ArH), 8.25-8.30 (m, 3H, H-2, H-9, H-15, ArH), 7.89 (d, 1H, H-18, J = 2.8 Hz, ArH), 7.73-7.79 (m, 1H, H-16, ArH), 6.52 (d, 2H, H-c, H-d, J = 4.0 Hz, p-cymene ArH), 6.39 (d, 2H, H-e, H-f, J = 5.6 Hz, p-cymene ArH), 2.76-2.82 (m, 1H, H-h, p-cymene aliphatic -CH proton), 2.34 (s, 3H, H-a, p-cymene aliphatic -CH 3 proton), 1.06 (d, 6H, H-i, H-j, J = 6.8 Hz, p-cymene isopropyl -CH 3 protons); 13 C NMR (CDCl 3 , 100 MHz): δ 158.6, 158.4, 151.4, 148.2, 147.9, 140.1, 139.4, 135.7, 135.4, 132.1, 129.8, 129.6, 128.2, 123.8, 112.7, 112.5, 105.5 ( p-cymene ArC), 104.1 ( p-cymene ArC), 87.0 ( p-cymene ArCH), 84.64 ( p-cymene ArCH), 31.3 (isopropyl -CH), 22.3 (isopropyl -CH 3 ), 19.17 (-pcymene -CH 3 ); 19 F NMR (CDCl 3 , 376 MHz): δ −71.07 (PF 6 ), −69.19 (PF 6 ) −61.41 (-F); 31 P NMR (CDCl 3 , 162 MHz): δ −152.99 to −135.43 (PF 6 ); HRMS (MeOH): m/z = 571.0657 [M − PF 6 ] + . Calculated 571.0639; anal.…”
mentioning
confidence: 99%
“…AST is found in both mitochondria and the cytosol, while ALT is found only in the cytosol [ 66 ]. Therefore, ALT is a more accurate indication of the detection of hepatocellular damage [ 7 , 63 ]. In a study of the literature, in parallel with our findings, in the blood samples of rats with sepsis caused by LPS; it has been reported that ALT, AST, and ALP enzymes were found to be significantly higher in the sepsis group [ 42 ].…”
Section: Discussionmentioning
confidence: 99%